3(n-6)+n=4-2(n-1)

Simple and best practice solution for 3(n-6)+n=4-2(n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(n-6)+n=4-2(n-1) equation:


Simplifying
3(n + -6) + n = 4 + -2(n + -1)

Reorder the terms:
3(-6 + n) + n = 4 + -2(n + -1)
(-6 * 3 + n * 3) + n = 4 + -2(n + -1)
(-18 + 3n) + n = 4 + -2(n + -1)

Combine like terms: 3n + n = 4n
-18 + 4n = 4 + -2(n + -1)

Reorder the terms:
-18 + 4n = 4 + -2(-1 + n)
-18 + 4n = 4 + (-1 * -2 + n * -2)
-18 + 4n = 4 + (2 + -2n)

Combine like terms: 4 + 2 = 6
-18 + 4n = 6 + -2n

Solving
-18 + 4n = 6 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
-18 + 4n + 2n = 6 + -2n + 2n

Combine like terms: 4n + 2n = 6n
-18 + 6n = 6 + -2n + 2n

Combine like terms: -2n + 2n = 0
-18 + 6n = 6 + 0
-18 + 6n = 6

Add '18' to each side of the equation.
-18 + 18 + 6n = 6 + 18

Combine like terms: -18 + 18 = 0
0 + 6n = 6 + 18
6n = 6 + 18

Combine like terms: 6 + 18 = 24
6n = 24

Divide each side by '6'.
n = 4

Simplifying
n = 4

See similar equations:

| V-9=-10 | | x+(x+200)+3(x+200)=1775 | | 5.2+0.7=2.8+2.2 | | x+(x+200)+3(x+200)= | | -16+y=2y | | 3(z-7)=12 | | 2.49+1.24b=11.17 | | 3g+5=21+g | | 4=-2x+5x+4 | | 3(5)-3x=9 | | 3(2-7)=12 | | 64-2x=75-3x | | 9x+4-5x=-18 | | 8(k-8)=8k-24 | | -18m=92 | | -k+18=15 | | 2x^2+2y^2+8x-8y-2=0 | | X+(x-1081)=213483 | | 92=-18m | | (17x-y)+(12x+4y)+90=180 | | 8x-3x-10=222 | | -1+3(a+4)=11+3a | | 2+2.4w=-10 | | 18-3.8t=7.36-1.9x | | 2(n+4)+2n=7n+29 | | 3x-38=2x+12 | | 6-6k=5k-10 | | 0.06x+.36y=1.56 | | -2x+6i=5+9yi | | 4x-16=44 | | 5(4x)-0.5x=234 | | -2+6i=5+9i |

Equations solver categories